Revisiting the Federal Character Principle in the Nigerian Public Service - Kehinde Abiodun, Isinkaye (LPPM Universitas Jambi, 2025)
The paper assessed the application of the federal character policy to the management of the public bureaucracy in Nigeria. It traces the genesis of the policy to the urgent need to ensure balanced, ethnic representation in the public service in the country. The paper posits that there are many challenges faced the operation of the policy such as statism, ethnic consciousness, and influence of party politics and political patronage. It concludes that the policy is indispensable in the Nigerian public service and it only need to be strengthened through fairness, objectivity and the use of appropriate sanctions when it is violated through omission by the body that is saddled with the role of managing the affairs of the commission. The paper utilized historical research design. Data analysis is interpretive because it describes the present situation in terms of the past events through the examination of documents, publications and people accounts of the past. Secondary data were sourced from published and unpublished sources for the research work. The paper concludes that federal character commission should be strengthened; this can be done through the provision of adequate finance and strengthening of their legal act and other enabling laws. The paper recommended among others that adequate sanctions should be applied where vagrant violations of the laid down rules and formula have been discovered in the operation of the organization in order not to give room for ethnic friction in the country.